Review on the Major Failure Cases of Unlined Pressure Shafts/Tunnels of Norwegian Hydropower Projects - Panthi, Krishna Kantha; Basnet, Chhatra Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
The Norwegian hydropower industry has more than 100 years of experience in constructing the unlined pressure shafts and tunnels. Most of the hydropower projects have long waterway systems consisting unlined high pressure shafts, underground powerhouse cavern, headrace and tailrace tunnels. The maximum static head reached with unlined pressure shaft and pressure tunnel concept is 1047 meter, which is equivalent to almost 10.5 MPa. It is obvious that the rock mass in the periphery of unlined shafts and tunnels experience high hydrostatic pressure exerted by the flowing water discharge. Experienced gained from the construction and operation of these unlined pressure shafts and tunnels were useful to develop design criterion and principles applied here in the Scandinavia. This paper reviews some of the first attempts of the use of unlined pressure shaft and tunnel concepts, highlights major failure cases, reviews and evaluates the triggering factors for the failure and also discusses about the gradual development of design criterion for the unlined pressure shafts and tunnels. The authors consider this review is a first step in the upgrade on this innovative concept, which could be used in other geological and tectonic environment than of the Scandinavia, such as in the Himalaya. HYDRO Nepal Journal of Water Energy and Environment Volume- 18, 2016, January Page -6 to 15